Addressing corticosteroid insensitivity in adults with asthma. (1st February 2016) - Thomson, Neil C.
Abstract: Corticosteroids are the most effective treatment for asthma, but the therapeutic response varies markedly between individuals, with up to one third of patients showing evidence of insensitivity to corticosteroids. This article summarizes information on genetic, environmental and asthma-related factors as well as demographic and pharmacokinetic variables associated with corticosteroid insensitivity in asthma. Molecular mechanisms proposed to explain corticosteroid insensitivity are reviewed including alterations in glucocorticoid receptor subtype, binding and nuclear translocation, increased proinflammatory transcription factors and defective histone acetylation. Current therapies and future interventions that may restore corticosteroid sensitivity in asthma are discussed, including small molecule drugs and biological agents. In the future, biomarkers may be used in the clinic to predict corticosteroid sensitivity in patients with poorly controlled asthma.